2018
DOI: 10.1051/matecconf/201816502005
|View full text |Cite
|
Sign up to set email alerts
|

Influence of defects on axial fatigue strength of maraging steel specimens produced by additive manufacturing

Abstract: Nowadays many materials such as steels, aluminium and titanium alloys can be realised by powder bed solutions melting subsequently powder layers by means of a laser or electron beam (Laser Beam Melting -LBM and Electron Beam Melting -EBM). The microstructure realised by layer-by-layer solidification having high cooling rate cannot be considered isotropic. Therefore, the mechanical properties could be influenced by the building direction. Regarding maraging steel, the study of the influence of the building dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…However, Yadollahi et al [10] on SLM 17-4-PH, Brandl et al [19] on SLM AlSi10Mg, Shamsaei et al [13] on DMD Ti6Al4V, Mower et al [8] on DMLS 316L and Rigon et al [20] on SLM maraging steel 18Ni300 showed a higher fatigue strength of horizontally built specimens compared to a vertical building direction, which corresponds to the observations for monotonic loading. Note that Rigon et al [20] additionally reported a higher fatigue strength of vertical building direction for another batch of used powder, indicating a significant influence of the used powder on the resulting mechanical properties. This corresponds to the work of Zhang et al [21] who also showed a higher fatigue strength in vertical building direction for SLM 316L.…”
Section: Introductionmentioning
confidence: 63%
“…However, Yadollahi et al [10] on SLM 17-4-PH, Brandl et al [19] on SLM AlSi10Mg, Shamsaei et al [13] on DMD Ti6Al4V, Mower et al [8] on DMLS 316L and Rigon et al [20] on SLM maraging steel 18Ni300 showed a higher fatigue strength of horizontally built specimens compared to a vertical building direction, which corresponds to the observations for monotonic loading. Note that Rigon et al [20] additionally reported a higher fatigue strength of vertical building direction for another batch of used powder, indicating a significant influence of the used powder on the resulting mechanical properties. This corresponds to the work of Zhang et al [21] who also showed a higher fatigue strength in vertical building direction for SLM 316L.…”
Section: Introductionmentioning
confidence: 63%
“…When examining fractured surface studies, it is known that defects of AM components mainly cause fatigue damage. These defects are referred to in the literature as lack of fusion (LoF) deficiency (Rigon et al, 2018). Following the literature, such defects are irregular in shape and are mainly found in both the surface and the subsurface area of the component.…”
Section: Resultsmentioning
confidence: 99%
“…Rigon et al researched the effect of printing orientation and heat treatment on static and axial fatigue strength of samples produced by laser beam melting (LBM) and electron beam melting (EBM). They reported a large distribution in the fatigue test results due to surface and subsurface defects (Rigon et al, 2018). Antunes et al examined fatigue crack growth in 18Ni300 steel produced with selective laser melting (SLM) in their study, wherein they obtained typical da/dN curves in C(T) samples and reported that a relatively low level of crack tip plastic deformation was observed (Antunes et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, this paper aimed at partially filling this gap, by investigating the fatigue property of Ti-6Al-4V parts manufactured by SLM. This is of significant interest for many industrial applications and would allow the design of safer products and components subjected to cyclic loadings [31][32][33].…”
Section: Introductionmentioning
confidence: 99%